The Role Of TikTok In Shaping Gen Z Students' English Vocabulary Proficiency - Pianasari, Pianasari; Faruk, Ahmad (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This study explores the role of TikTok in shaping English vocabulary skills in Generation Z students at SMK Nusantara Bangorejo. The development of digital technology, especially social media platforms such as TikTok, has created a significant informal learning space for the digital native generation. The research aims to identify patterns of consumption of English-language content, analyze the types of vocabulary acquired, evaluate the effectiveness of TikTok as a learning resource, and develop a conceptual framework for its integration in formal learning. Using a qualitative approach, the data was collected through semi-structured interviews with 20 students and one English teacher, as well as indirect observation of student activity on TikTok. The results of the study showed that 75% of participants experienced an increase in English vocabulary after accessing TikTok regularly, with a preference for song, vlog, and game-based educational materials. The platform facilitates the acquisition of contemporary and informal vocabulary that is rarely encountered in formal curricula through incidental learning. Key challenges include the gap between passive recognition and active production of vocabulary, as well as potential addiction. It is concluded that TikTok has the potential to be an effective pedagogical tool when it is integrated in a structured manner with digital literacy in mind, through a conceptual framework that includes a social media responsive curriculum, authentic content-based pedagogy, informal learning assessments, and digital literacy development.